Exploring the influence of intersecting social identities on the leadership experience of female managers in the South African health system - Reddy, Mishka (University of Cape Town, 2021)
In the transition from the Millennium Development Goals to the Sustainable Development Goals, the importance of an integrated health system in which all health activities interact - including the multiple actors within the system - has gained greater recognition. In light of these transitions, the World Health Organisation and the Alliance for Health Policy and System Research called for a participatory leadership model, which engages with multiple health system actors in and out of the health system. It is a leadership model, which seeks to be inclusive of diverse and currently underrepresented stakeholders such as women. This leadership model is aligned with the gender equality movement in health leadership, which has rightfully gained global prominence over the last decade. However, it would be an oversimplification to assume all women in leadership positions have had to overcome similar obstacles. Treating women as a homogenous group tends to leave people out given the evidence that social identities culminate to produce unique experiences and therefore challenge feminist notions of the homogeneity of women. Drawing on data from a primary study on gender and leadership in South Africa, this study sought to explore the influence of gender, as it intersects with race and professional cadre, on the experiences of female health managers in the South African health system. The primary study noted that black females felt as though they were "left behind" throughout their leadership journey. This secondary analysis was undertaken using Bilge's intersectionality approach. It is a two-step qualitative analysis approach, which uses an understanding of intersectionality to extract data related to social identity and intersecting social identities. The analysis assessed 1) how gender, race and professional cadre discretely inform each participant's account and 2) how gender intersects with other social identities to create unique barriers for different women. It explored how intersecting identities might leave certain people behind - and how then to conduct health policy and systems research that can produce qualitative data necessary for creating formalised initiatives that address potential barriers. While recognising the enormous potential of participatory leadership, this study focused on the experiences of formally designated health managers who were able to reflect on their journey towards their current position and explain the barriers in this journey, related to their entangled social identities.